ANALISIS DAN PERANCANGAN SISTEM INFORMASI ABSENSI DAN PENGGAJIAN BERBASIS WEBSITE PADA CV LUNA - Maulana, Reza; Firmansyah, Yoki; Apriyanti, Diana (STMIK KAPUTAMA, 2024)
This research was conducted to analyze and create an attendance and payroll information system program for CV Luna. In carrying out its operational activities, especially in employee attendance data and payroll processing, a manual system is currently being used, leading to frequent errors. The manual system in place at CV Luna has weaknesses, including the lengthy time required for payroll calculations due to poorly recorded attendance data and the risk of errors in salary calculations that could benefit or harm one of the parties involved. From these issues, the idea of creating a web-based information system emerged, which can automate employee attendance and payroll management. In the system design, the research used the waterfall method and employed the PHP Codeigniter Framework. There are two users who can access this system: employees and the finance department. Employees can only record their attendance, while the finance department can access attendance summaries, salary reports, and payslips. This computerized system makes it easier for employees to record their attendance and for the finance department to generate employee salary reports.